Momordica genus in Asia - An Overview - Bharathi, L.K; John, K Joseph (Springer India : Imprint: Springer, 2013)
Asiatic Momordica comprises 10 species of which 3 are monoecious and rest dioecious. They are unique in the sense that all are wild or cultivated vegetables with medicinal uses. Barring bitter gourd, all are under utilized vegetables with little research and conservation efforts. In this book, the authors have presented the available information on various aspects of Asiatic Momordica like taxonomy, cytogenetics, crop improvement, origin, ethnobotany and crop production at one place. The book is well illustrated with color maps and photographs depicting habit, morphology and distribution of individual taxa. Species distribution map for all Indian taxa, descriptor for characterization and preliminary evaluation of dioecious and monoecious group available varieties, keys for botanical identification are some of the unique features of the book. The book will be useful to botanists, horticulturists, foresters, environment educators, conservation biologists, plant science students in general and all interested in agrobiodiversity.